Prioritization of predisposing factors of gingival hyperplasia during orthodontic treatment: the role of amount of biofilm - Séverine Vincent-Bugnas; Leslie Borsa; Apolline Gruss; Laurence Lupi (BMC, 2021)
Abstract Background The mechanism of gingival growth that may occur during fixed orthodontic treatment is not yet fully understood and the amount of dental plaque is often incriminated. The objective of this study was to evaluate the prevalence of gingival growth during multi-attachment orthodontic treatment and to prioritize its predicting factors, especially the quantity of biofilm. Methods This comprehensive cross-sectional descriptive study was conducted on orthodontic patients aged 9 to 30 years, in good health, treated by a fixed appliance. Periodontal clinical parameters such as plaque index, gingival index, probing pocket depth, periodontal phenotype and gingival enhancement index were recorded. Likewise, the brushing habits and the date of the last scaling were noted. The orthodontic parameters studied were the duration of the treatment, the type of bracket, the alloys used for the arches and the type of ligatures. Descriptive statistics were carried out, and variables presenting p value < 0.25 were included in a multivariate analysis to calculate the Odds Ratio (OR) of gingival enlargement". Results A total of 193 patients were included (16.38 ± 4.89 years). Gingival growth occurred for 49.7% of patients included. The predisposing factors for this pathology during fixed orthodontic treatment were conventional metal brackets (p = 0.021), mouth breathing (p = 0.040), male gender (p = 0.035), thick periodontal phenotype (p = 0.043), elastomeric ligations (p = 0.007), duration of treatment (p = 0.022) and presence of plaque (p = 0.004). After achievement of the logistic regression, only two factors remained related to gingival enlargement: metallic brackets (OR: 3.5, 95% CI: 1.1-10.55) and duration of treatment (OR: 2.03, 95% CI: 1.01-4.08). The amount of plaque would not be directly related to the development of gingival increase during orthodontic treatment. Conclusions Among the predisposing factors that underlie gingival growth during multi-attachment therapy, the amount of plaque is not found. The qualitative assessment of the plaque and its evolution during treatment could clarify the role of the biofilm in the occurrence of gingival overgrowth.